Review on Knowledge Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The goal of this paper is to address the important relationship between the High Performance Working System (HPWS) as the main component of Strategic Human Resource Management (SHRM) and organizational performance as the basis for the determination of sustainable competitive advantage. It also explores the link between HR strategy and business strategy. Findings validated the relationship between SHRM-HPWS and financial as well as non-financial (employee outcome) organizational performance based on literature review as evidenced. HR strategy is also related to business strategy as it leads to maintaining high-quality customer satisfaction, delivering high-quality, loving employees and sustaining employee dedication and commitment to the company for effective and sustainable competitive advantage. It thus strengthens employee growth, motivation and willingness to remain in the business for longer. To conclude, to retain the competitive advantage, organizational efficiency can be achieved through various sources. The conceptual framework often reflects how the research comes to an end.